2022
DOI: 10.1038/s41598-022-25533-3
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight cost-effective hybrid materials for energy absorption applications

Abstract: The present paper experimentally explores the influence of the fiber hybridization and layering sequence on crashworthiness behavior and deformation history of polymer/metal thin-walled pipes. Jute (J)/glass (G) reinforced epoxy over wrapped aluminum (Al) pipes were prepared via hand wet wrapping then subjected to axial quasi-static compressive loads. The load versus displacement plots and crashing indicators, i.e. peak crushing load ($${\mathrm{F}}_{\mathrm{ip}}$$ F … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…[22] It has been effectively used by many authors in the literature. [22,24,25,[35][36][37] The mechanical characteristics of the reinforcements and matrix employed in this study are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] It has been effectively used by many authors in the literature. [22,24,25,[35][36][37] The mechanical characteristics of the reinforcements and matrix employed in this study are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Based on numerous studies, a crosshead speed of 10 mm/min was chosen for uniaxial quasi-static crush testing. [37,[39][40][41] Test specimens were set up between two flat steel plates that were parallel to each other before the test start. An autonomous data collection system was used to directly record loaddisplacement data.…”
Section: Test Descriptionmentioning
confidence: 99%
“…51,52 Others performed the tests at V = 5 mm/min 5355 . However, Ma and Yan 56 and Abd El-baky et al 57,58 selected V = 10 mm/min in their scholarships. In this study, the researchers tried to understand how crosshead speed affected the crushing attitude of the thin-walled, induced-hole (GFRP) tubes.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…17 Because of these advantages, natural fibers are a viable option for completely or partially replacing synthetic fibers in various applications. 813 Despite their attraction, they have some difficulties when compared to synthetic fibers, including high variability, poor moisture resistance, weaker mechanical qualities, and lower impact resistance. 14,15…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Because of these advantages, natural fibers are a viable option for completely or partially replacing synthetic fibers in various applications. [8][9][10][11][12][13] Despite their attraction, they have some difficulties when compared to synthetic fibers, including high variability, poor moisture resistance, weaker mechanical qualities, and lower impact resistance. 14,15 Jute (J) is one of the most promising natural fibers because of its low cost, light weight, moderate mechanical properties, low thermal conductivity, moderate moisture regain, and vast production.…”
Section: Introductionmentioning
confidence: 99%